ANALISIS KETERLIBATAN ORANG TUA DALAM MELAKSANAKAN PEMBELAJARAN DARING DI SEKOLAH DASAR - Pratiwi Silvia Rahman; Arsyi Rizqia Amalia; Din Azwar Uswatun (Universitas Ngudi Waluyo, 2022)
This study aims to describe the implementation of online-based learning in high grade SDN Gunungpuyuh CBM, and to describe the involvement of parents in online learning at SDN Gunungpuyuh CBM. This study used a descriptive qualitative approach and the research subjects were teachers and grade 5 students, totaling 24 students. The data collection technique used was in the form of interviews with teachers and questionnaires given to students via google form. The data analysis technique starts from data reduction, data presentation and conclusion drawing. The results of this study indicate that parental involvement in online learning in elementary schools is slightly different from face-to-face learning to online learning. When during face-to-face learning, the role of parents is not too involved. When carrying out learning, it is different from online learning, parental involvement is needed to support the spirit of student learning at home. In addition, there are several inhibiting factors that are the reason students are less enthusiastic in carrying out online learning.